Beyond nitrate transport: AtNRT2.4 responds to local and systemic nitrogen signaling in Arabidopsis - Huaifang Zhang; Jinxia Huang; Yanmei Li; Jinling Zhao; Weitao Mai; Luqman Khan; Meng Zhang; Wenquan Wang; Changying Zeng; Xin Chen (BMC Plant Biology)
Abstract Background Plants have evolved the ability to detect nitrogen fluctuations to optimize their nitrogen acquisition. However, the mechanisms of nitrogen perception and signaling still need to be well characterized. Results Through split-root experiments, this study demonstrated that nitrate transporter 2.4 (AtNRT2.4) can respond to both local and systemic nitrate signals, modulating the transcription of genes such as AtANR1 and AtCIPK23, thereby altering root architecture. Beyond merely detecting the fluctuations of environmental nitrate concentrations, AtNRT2.4 was actively engaged in the dual-affinity transition of AtNRT1.1 and suppressed the expression of AtNLP7, which is crucial for responding to intracellular nitrate signals. Notably, AtNRT2.4 did not participate in the CEP-mediated systemic nitrogen stress signaling pathway and also did not require AtNRT3.1 as a chaperone protein. The knockout of AtNRT2.4 did not affect the growth of Arabidopsis thaliana under low nitrate conditions. However, its overexpression significantly enhanced biomass accumulation and seed yield under normal nitrate concentrations. Furthermore, under nitrate deficiency stress, AtNRT2.4 induced the expression of key genes involved in anthocyanin synthesis and accumulation, thereby promoting anthocyanin accumulation in leaves. Conclusions In summary, AtNRT2.4 plays a crucial role in local and systemic nitrate signals sensing, adjustment of root architecture, and anthocyanin accumulation, providing new insights into how plants respond to nitrogen deprivation.